Proceedings of the 15th International Conference on Emerging Networking Experiments and Technologies 2019
DOI: 10.1145/3359989.3365410
|View full text |Cite
|
Sign up to set email alerts
|

PURR: a primitive for reconfigurable fast reroute

Abstract: Highly dependable communication networks usually rely on some kind of Fast ReRoute (FRR) mechanism which allows to quickly reroute traffic upon failures, entirely in the data plane. This paper studies the design of FRR mechanisms for emerging reconfigurable switches. Our main contribution is an FRR primitive for programmable data planes, PURR, which provides low failover latency and high switch throughput, by avoiding packet recirculation. PURR tolerates multiple concurrent failures and comes with minimal memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
0
16
0
5
Order By: Relevance
“…As future work, we plan to integrate IntSight with mechanisms to solve the diagnosed SLO violation problems. An attractive future direction is to coordinate quick reactions (that can be activated by the data plane right after an SLO violation is detected, e.g., in line with [8]) with longer-term, strategic decisions, which would work in the control-plane timescale.…”
Section: Resultsmentioning
confidence: 99%
“…As future work, we plan to integrate IntSight with mechanisms to solve the diagnosed SLO violation problems. An attractive future direction is to coordinate quick reactions (that can be activated by the data plane right after an SLO violation is detected, e.g., in line with [8]) with longer-term, strategic decisions, which would work in the control-plane timescale.…”
Section: Resultsmentioning
confidence: 99%
“…As first recovery concepts for programmable data planes are emerging, researchers also started investigating general primitives to support an efficient recovery. For example, Chiesa et al [263], [268] suggested an FRR primitive which requires just one lookup in a TCAM, and hence outperforms naive implementations as it avoids packet recirculation. This can improve latency and throughput, and, if deployed as a "primitive", can be used together with many existing FRR mechanisms (which is also demonstrated, e.g., for [269]), allowing them to benefit from avoiding packet recirculation.…”
Section: Recovery Concepts In Programmable Data Planesmentioning
confidence: 99%
“…At the same time, new designs will remain constrained by the limitations of programmable devices and by increasing performance requirements. A good example illustrating the trade-off between the resource utilization and performance (in terms of latency and throughput) has been presented in [268].…”
Section: Classification Summarymentioning
confidence: 99%
“…Most recently, in the context of P4, Chiesa et al [254], [258] suggested an FRR primitive for programmable dataplanes based on P4. Their solution requires just one lookup in a TCAM, and hence outperforms naive implementations as it avoids packet recirculation.…”
Section: B Programmable Data Planes and P4mentioning
confidence: 99%
“…At the same time, new designs will remain constrained by the limitations of programmable devices and by increasing performance requirements. A good example illustrating the trade-off between the resource utilization and performance (in terms of latency and throughput) has been presented in [258]. Based on the specific subset of parameters which are used by an algorithm to determine the preferred alternative output network interface, the corresponding actions may also be triggered if necessary, both in the context of messages as well as the entire forwarding pipelines maintained by network devices, for example:…”
Section: Classification Summarymentioning
confidence: 99%